Trajectories, institutions, and re-locations: a conversation on Inter-Asia outside Asia. Issue 2 (3rd April 2019) - Lee, Christopher; Chen, Kuan-Hsing; Gunew, Sneja; O'Brien, Michelle; Yue, Audrey; Alam, Rusaba
ABSTRACT: This conversation explores the resonances of the Inter-Asia project outside the geographical boundaries of Asia. The participants, who represent diverse national, institutional, and professional experiences, discuss the following topics: how Asia and the Inter-Asia project has affected their intellectual trajectories; navigating academic institutions and formations; the changing meaning of diaspora and migration and their effects on language and communication; and the relationship between the academy and social movements. Particular attention is paid to reframing Australia and Canada from an Inter-Asia perspective.